Development of TOAFL Media Based on Learning Management System For IAIN Metro Students | Pengembangan Media TOAFL Berbasis Learning Management System bagi Mahasiswa di IAIN Metro - Nawang Wulandari (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This research aims to develop TOAFL test media at IAIN Metro Language Development Unit. This research is a type of research development or Research and Development (R&D). The development model of this research is the ADDIE model developed by Reiser and Mollenda. The stages of development in this research are analysis, design, development, implementation and evaluation. The subject of this study is the IAIN Metro Language Development Unit. Data collection techniques used in this study were questionnaires, documentation and interviews. The collected data is analyzed using a percentage formula. Based on the validation results of the experts then converted to the table of media eligibility interpretation criteria, it can be explained that the feasibility of maharah istima' questions is 92%, the feasibility of qowaid questions is 89%, the feasibility of Maharah Qira'ah questions is 97% and the feasibility of media developed is 79%. It can be concluded that the development of TOAFL media and test instruments is included in the very feasible category. The weakness of this study is that the media produced requires many stages in this log process, hopefully the next researcher can develop a more efficient and up-to-date test media.